THE DEVELOPMENT OF REINFORCEMENT COMMUNITY ECONOMY'S MODEL OF CULTURAL CAPITAL IN KO KRET, NONTHABURI PROVINCE - สาโรจน์, ทรงยศ; แสงเงิน, สุพจน์ (Academic Journal Phranakhon Rajabhat University, 2020)
This research is Mixed Method Research based on the Quantitative Research and Qualitative Research Sample population and stakeholders : Government sector, Private sector, Ko Kret Community and Academic . This research was objectives of this study were to explore related context of cultural capital, to develop reinforcement community economy’s model of cultural capital, and to evaluate reinforcement community economy’s Model of cultural capital. The methodology of this study included Documentary Analysis, Participatory Observation, and In-Depth Interview, Community Enterprise Promotion Division, Department of Agricultural Extension of 2018 .Data were analyzed by using mean. The results of this research showed that: Ko Kret Community was established since the Ayutthaya era. Formerly for Boat checkpoint and trading purposes. Therefore. Nowadays, this community manages the relationship with public sector and outsiders in order to create trading and social network. Its adaptation mainly is reflected as transformation of various occupation, values and opinions. Since its knowledge management is conducted through the education system. Reinforcement community economy’s model of cultural capital consists of six sub- Parts: 1) Part of Cultural capital, Part of Integration, 3) Part of Knowledge, Part of Environment, Part of A model for guideline application and Part of The successful condition. The evaluation of the developed model indicated had score of 78.75. This figure was considered as high score compared to the standard score of 2018 community enterprise assessment, Community Enterprise Promotion Division, Department of Agricultural Extension.